PHYSICOCHEMICAL PROPERTIES OF WATER CHARACTERIZATION IN PETITENGET TEMPLE ESTUARY, BADUNG REGENCY - Putu Suantara; Anak Agung Ketut Sudiana; I Made Wahyu Wijaya; I Ketut Sumantra (International Journal of Applied Science and Sustainable Development (IJASSD), 2020)
A water quality deterioration has been predicted in the estuary area near a tourism spot, namely Petitenget Temple. It is located on the north side of Badung Regency, Bali Province. Brownish color and odor from the water were found in the preliminary study. There were 4 samples along the river that is ended up in the estuary of Petitenget Temple. This study aims to respond to the regional regulation about environment quality standards and deterioration level. Laboratory analysis was conducted to measure physical and chemical parameters. The result shown that the concentration of suspended solid was in the range of 7 – 18 mg/L, the temperature was in the range of 270C – 290C, pH of 6,2-7,3 and 9,2-12,5 NTU for turbidity. Chemical parameters shown the range of COD was 22,68-61,50 mg/L, BOD 11,42 – 26,74 mg/L, 0,45-1,35 mg/L for nitrogen in form of ammonia, 0,20 - 0,68 mg/L for orthophosphate, iron was 0,04 – 0,87 mg/L and there was no lead (Pb) detected. Based on the discussion, the physicochemical characteristic of water in the estuary of Petitenget Temple belonged between Class II and III. According to these results, the water along the estuary of Petitenget Temple was polluted and a treatment approach is urgently needed.